ANALYSIS OF ROUTINE ELECTROENCEPHALOGRAPHIC ABNORMALITIES IN PATIENTS WITH CHRONIC ALCOHOL DEPENDENCE AND RELATED FACTORS (Vietnam Journal of Community Medicine, 2026)
Objective: To describe clinical features and routine electroencephalogram findings, and to assess associations between electroencephalogram abnormalities and clinical factors in patients with chronic alcoholism.Methods: A cross-sectional descriptive study was conducted on 67 patients with chronic alcoholism treated at the Department of Psychiatry, Military Hospital 103 from January 2023 to December 2025.Results: The mean age was 45.8 ± 8.6 years; males accounted for 92.5% of the sample. A drinking duration of ≥ 10 years was observed in 65.7% of patients; the rates of alcohol withdrawal seizures and delirium tremens were 26.9% and 17.9%, respectively. The prevalence of abnormal electroencephalogram was 52.2%, with diffuse background slowing being the most common abnormality (35.8%). Abnormal electroencephalogram was significantly associated with age ≥ 45 years (OR = 4.22; p = 0.005), drinking duration ≥ 10 years (OR = 5.48; p = 0.002), average alcohol consumption ≥ 500 mL/day (OR = 3.03; p = 0.030), alcohol withdrawal seizures (OR = 4.67; p = 0.011), and delirium tremens (OR = 6.00; p = 0.017).Conclusion: Electroencephalogram abnormalities were present in more than half of patients with chronic alcoholism, predominantly as diffuse background slowing. Older age, prolonged alcohol use, and severe withdrawal manifestations were associated with electroencephalogram abnormalities.
Keywords: Electroencephalogram, chronic alcoholism, alcohol withdrawal, withdrawal seizures.